The Influence of Loan at Risk and Bank Spesific Variables on The Profitability of Commercial Banking in Indonesia Based on Core Capital: Period 2015 to 2022 - Hadi, Astomo (Syntax Literate, 2024)
This research aims to examine the influence of loan at risk (LAR) and other specific bank variables, namely size, leverage, and capital, on the profitability of commercial banks in Indonesia based on the classification of core capital set by banking authorities. The study utilizes panel data regression with a balanced fixed-effect model from a sample of 67 examined commercial banks, both in aggregate and based on the core capital classification of each bank, covering the research period from 2015 to 2022. The results indicate that the credit asset portfolio with LAR quality significantly affects the profitability of commercial banks negatively, both in terms of ROA and ROE, applying to the entire group of commercial banks studied. Meanwhile, other specific variables have varying degrees of influence and significance. Collectively, the independent variables in all research models have a significant impact on the profitability of all commercial banks in Indonesia. The findings of this study can contribute to the reference for bank management and other stakeholders in assessing the profitability performance of commercial banks, as well as expanding the literature in the field of banking.